Chest CT‐assessed comorbidities and all‐cause mortality risk in COPD patients in the BODE cohort. Issue 4 (7th February 2022) - Ezponda, Ana; Casanova, Ciro; Divo, Miguel; Marín‐Oto, Marta; Cabrera, Carlos; Marín, Jose M.; Bastarrika, Gorka; Pinto‐Plata, Víctor; Martin‐Palmero, Ángela; Polverino, Francesca; Celli, Bartolome R.; de Torres, Juan P.
Abstract: Background and objective: The availability of chest computed tomography (CT) imaging can help diagnose comorbidities associated with chronic obstructive pulmonary disease (COPD). Their systematic identification and relationship with all‐cause mortality have not been explored. Furthermore, whether their CT‐detected prevalence differs from clinical diagnosis is unknown. Methods: The prevalence of 10 CT‐assessed comorbidities was retrospectively determined at baseline in 379 patients (71% men) with mild to severe COPD attending pulmonary clinics. Anthropometrics, smoking history, dyspnoea, lung function, exercise capacity, BODE (BMI, Obstruction, Dyspnoea and Exercise capacity) index and exacerbations rate were recorded. The prevalence of CT‐determined comorbidities was compared with that recorded clinically. Over a median of 78 months of observation, the independent association with all‐cause mortality was analysed. A 'CT‐comorbidome' graphically expressed the strength of their association with mortality risk. Results: Coronary artery calcification, emphysema and bronchiectasis were the most prevalent comorbidities (79.8%, 62.7% and 33.9%, respectively). All were underdiagnosed before CT. Coronary artery calcium (hazard ratio [HR] 2.09; 95% CI 1.03–4.26, p  = 0.042), bronchiectasis (HR 2.12; 95% CI 1.05–4.26, p  = 0.036) and low psoas muscle density (HR 2.61; 95% CI 1.23–5.57, p  = 0.010) were independently associated with all‐cause mortality and helped define the 'CT‐comorbidome'. Conclusion: This study of COPD patients shows that systematic detection of 10 CT‐diagnosed comorbidities, most of which were not detected clinically, provides information of potential use to patients and clinicians caring for them. Abstract : This multicentric study shows that chest computed tomography (CT) to evaluate the presence of 10 comorbidities detects important pathologies not diagnosed in the clinical management of those patients. While emphysema, coronary artery calcification (CAC) and bronchiectasis were the most prevalent CT‐detected comorbidities, CAC, bronchiectasis and low Psoas muscle density were independently associated with all‐cause mortality. See related Editorial